2020
DOI: 10.1186/s12889-020-8430-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the food safety knowledge and attitudes of food handlers in hospitals

Abstract: Background: The possession of inadequate food safety knowledge (FSK) by food handlers poses a serious threat to food safety in service establishments. The aim of this research was to investigate factors that influenced the FSK and food safety attitudes (FSA) of employees involved in the preparation and/or the serving of food from nine hospitals in the Capricorn District Municipality (CDM) in Limpopo Province, South Africa. Method: Up to 210 individuals (18-65 years) who were employed in these hospitals, and wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 48 publications
8
34
1
Order By: Relevance
“…(2010) , Stratev at al. (2017) , and Teffo and Tabit (2020) which reported that the level of education among the participants is not statistically significant to their self-reported FSP. An individual's educational attainment does not determine his or her application of food safety practice, since in this study, online food handlers with higher levels of education did not differ in their self-reported FSP, as compared to those with lower levels of education.…”
Section: Resultsmentioning
confidence: 89%
“…(2010) , Stratev at al. (2017) , and Teffo and Tabit (2020) which reported that the level of education among the participants is not statistically significant to their self-reported FSP. An individual's educational attainment does not determine his or her application of food safety practice, since in this study, online food handlers with higher levels of education did not differ in their self-reported FSP, as compared to those with lower levels of education.…”
Section: Resultsmentioning
confidence: 89%
“…Our finding affirms the assertion that training upsurges understanding of food safety which might reflect into hygiene practices [ 48 ]. Hence, a lack of or inadequate training of SCFHs on food safety may inadvertently result in poor hygiene practices, thereby encouraging food contamination [ 26 , 36 ]. This implies providing food safety training to food handles is important to keep consumers from food poisoning and other wellbeing dangers that could arise from eating unsafe food.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 25 ] study in China, among street food vendors, revealed poor behaviour practices and knowledge of food safety among the respondents. Tabit and Teffo [ 26 ] in South Africa found over 60% of the respondents keep good knowledge and acceptable hygiene performance of food safety. Lema et al [ 27 ] in Ethiopia reported that below half of the respondents obtained good food cleanliness applications.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect seems to be common in underdeveloped countries. Teffo and Tabit (2020) showed in their study that the majority of hospital food handlers were females and this could be linked to the fact that, in South Africa, there is a higher number of women than men in all nursing and food service occupations.…”
Section: Resultsmentioning
confidence: 99%
“…A study performed with food handlers in South Africa demonstrated that although the majority of food handlers possessed a satisfactory food safety knowledge only the minority gave correct answers to questions concerning foodborne bacteria and diseases. The study also showed that food handlers who had higher levels of education, more years of experience, and a higher job position, did not necessarily possess better food safety knowledge outcomes (Teffo & Tabit, 2020). Taking place in Beirut and Mount Lebanon, another study demonstrated that knowledge scores were significantly higher among food handlers who attended a training course, worked as public employees, and in hospitals that were not affiliated to universities.…”
Section: Introductionmentioning
confidence: 99%